Kinerja Lingkungan, Tekanan Stakeholder dan Kinerja Keuangan Perusahaan Manufaktur - Widianti, Ni Luh Putu Tika; Ariyanto, Dodik; Andreana, Made Oka Candra (E-Jurnal Akuntansi; Vol 34 No 5 (2024)DO - 10.24843/EJA.2024.v34.i05.p15, 2024)
The purpose of this study was to examine the effect of environmental performance and stakeholder pressure on the company's financial performance. The research was conducted on manufacturing companies listed on the IDX in 2019-2021. The research sample was determined by purposive sampling technique and obtained as many as 75 companies with 225 observational data. Data collection was carried out using non-participant observation methods. Using panel data regression analysis technique using the analysis tool eviews 10. The results showed that environmental performance has a significant positive effect on company financial performance, Environmental Sensitive Industry (ESI) has a negative effect on company financial performance. Meanwhile, Customer Proximity Industry (CPI), Investor Oriented Industry (IOI) and Employee-Oriented Industry (EOI) have no effect on the company's financial performance. Keywords: Financial Perfomance; Environmental Perfomance; Stakeholder Pressure